Rapid and Efficient Synthesis of Succinated Thiol Compounds via Maleic Anhydride Derivatization - Hiroshi Yamaguchi; Hikari Sugawa; Himeno Takahashi; Ryoji Nagai (Molecules)
Succination is a non-enzymatic post-translational modification of cysteine (Cys) residues, resulting in the formation of S-(2-succino)cysteine (2SC). While hundreds of 2SC-modified proteins have been identified and are associated with the dysfunction of proteins, the underlying molecular mechanisms remain poorly understood. Conventional methods for synthesizing succinated compounds, such as 2SC, often require prolonged reaction times and/or HCl hydrolysis. In this study, we present a rapid and efficient synthesis method for succinated compounds using maleic anhydride, enabling more effective in vivo studies of succination mechanisms. This method was tested on thiol compounds with varying molecular weights, including Cys derivatives, Cys-containing peptides, and reduced bovine serum albumin. By incubating these compounds in an aqueous buffer with maleic anhydride dissolved in an organic solvent like diethyl ether, we achieved significantly improved succination efficiency compared to conventional methods. The succination efficiency using maleic anhydride surpassed that of fumaric acid or maleic acid. Notably, this approach facilitated the succination of amino acids, peptides, and proteins within minutes at 25 °C, without requiring acid hydrolysis. Our findings provide a straightforward, time-efficient strategy for synthesizing succinated thiol compounds, offering a valuable tool to enhance the understanding of succination’s molecular mechanisms and its role in protein function and dysfunction.